2017
DOI: 10.1002/cmr.a.21459
|View full text |Cite
|
Sign up to set email alerts
|

An irregular sampler

Abstract: The historical evolution of sparse sampling methods in multidimensional NMR is important for understanding them in the context of developments outside of NMR. This brief, anecdotal history provides context, but also points to potential sources of insights into sparse sampling that have yet to be utilized in NMR.Advances in sparse sampling for multidimensional NMR represent a confluence of many disparate threads. K E Y W O R D Scompressed sensing, non-Fourier methods, nonuniform sampling, signal processing, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…ML strongly depends on training data, and getting experimental spectra is expensive (specially to get them assigned or labeled) and may result in sparse and unbalanced data sets. An interesting ML exercise providing a valuable lesson on the importance of training data was recently reported by Hoch . They tried to apply a ML algorithm (the details of the actual ML algorithm have not been disclosed) to find optimal sampling schedules for non‐uniformly sampled (NUS) NMR spectra.…”
Section: Signal Processingmentioning
confidence: 99%
“…ML strongly depends on training data, and getting experimental spectra is expensive (specially to get them assigned or labeled) and may result in sparse and unbalanced data sets. An interesting ML exercise providing a valuable lesson on the importance of training data was recently reported by Hoch . They tried to apply a ML algorithm (the details of the actual ML algorithm have not been disclosed) to find optimal sampling schedules for non‐uniformly sampled (NUS) NMR spectra.…”
Section: Signal Processingmentioning
confidence: 99%
“…[ 58–62 ] These applications have been successful enough that multiple versions of AlphaFold, developed by Google's DeepMind team, have performed best overall in the Critical Assessment of Techniques for Protein Structure Prediction (CASP) competition for two consecutive years. [ 63 ] AlphaFold2 has been used to predict the structures of all proteins in the human proteome plus those from an additional 20 organisms, resulting in 350 K structures initially and which has grown to 200 M. [ 59,64 ] Recently, it has been shown that protein sequences alone are sufficient to predict three‐dimensional structure in many cases. [ 61,62 ] While there is understandably a considerable amount of excitement for these achievements and their future implications, many challenges remain, especially as applied to drug discovery.…”
Section: Molecular Generationmentioning
confidence: 99%